Antioxidant Activity of the Methanolic Extract of Ricinus communis Leaves - KUMAR GUPTA, MAHESH; SHARMA, P.K.; SINGH, RAMESH; ANSARI, S.H. (Asian Journal of Chemistry, 2010)
Plants containing flavonoids have been reported to possess strong properties. The 50 % methanolic extract of Ricinus communis leaves was screened for in vitro and in vivo antioxidant properties using standard procedures. The methanol extract exhibited IC50 values of 41.40 ± 3.98 and 46.75 ± 08.73 μg/mL, respectively in DPPH and nitric oxide radical inhibition assays. These values were less than those obtained for ascorbic acid and quercetin, used as standards. In the in vivo experiments the extract treatment at 250 and 500 mg/kg body weight dose caused a significant increase in the level of the catalase in the liver and the kidneys. A significant increase in the level of SOD in the liver was observed. The treatment also caused a significant decrease in the TBARS and increase in the ascorbic acid levels. These results suggest strong antioxidant potential of the methanolic extract of Ricinus communis leaves.